Peculiarities of phytomass and mortmass formation in oak shelterbelts within the forest-steppe part of Kharkiv Region - Sydorenko, S. V.; Pasternak, V. P.; Sydorenko, S. H.; Hladun, H. B. (Forestry and Forest Melioration, 2019)
Introduction Shelterbelts that are part of the protective system, play a significant role in agricultural landscapes, they greatly improve climate and prevent land degradation. The components of protective stands carry out a long-term carbon sequestration and oxygen production. The aim of the research was to determine the ability of linear stands to adsorb carbon from the atmosphere and deposit it in the phytomass (trunks, bark, branches, and leaves) and mortmass (fine and coarse woody debris, litter) components. Materials and Methods To study phytomass and mortmass, we used the data from 20 field sampling sites located in the typical for the north-eastern part of the Left-Bank Forest-Steppe oak shelterbelts. The data were collected in accordance with the methodological approaches for the integrated assessment of the quantitative indicators of phytomass (roots, trunk, bark, leaves) and mortmass (fine and coarse woody debris and litter) components. On the sites, mortmass of the forest stands was also evaluated by fractions. In particular, we noted presence of dead trees, coarse and fine woody debris. Mortmass accounting was performed fractionally using the FIREMON methodology adapted for condition of Left-Bank Forest-Steppe. Coarse woody debris was classified according to the destruction degree, taking into account changes in the base density due to the destructive processes in timber. The forest litter was also recorded and mineralization layers were further determined. Results We established that the way the phytomass in a shelterbelt gets distributed depends on its structural features. With increasing shelterbelt’s vertical profile openness (%), the proportion of the aboveground phytomass increases accordingly. The phytomass stock of the stand in the shelterbelts depended on the overall productivity of the stand, as well as on the growing stock. We found that the phytomass in the linear stands was distributed as follows: trunk timber (59.3%), branches (26.6%), bark (9.9%) and leaves (4.3%). The undergrowth phytomass reached 23.1 tonnes per ha (from 1.5 to 23.1) and depended on the shelterbelt structure (r = -0.53) and width (r = 0.64). When calculating mortmass by fractions, we took into account changes in the base density brought about by destructive processes in timber. We established that the aboveground mortmass components varied from 2.5 to 41.0 tonnes per ha. We also found that absolute values of mortmass grow with an increase of the stand density (r = 0.37), which is explained by more intensive natural thinning. A similar tendency was observed for coarse woody debris. For this fraction, a moderate correlation between the mortmass increase and that of the phytomass of large undergrowth (r = 0.5) was also found. It is found out that the total carbon stock contained in phytomass of the shelterbelt ranges from 53.4 to 294.0 tonnes per ha and depends on the health and productivity of the linear protective forest stands. Conclusions We evaluated the shelterbelts’ potential capability to produce oxygen and store carbon for stands of the third development period. During the analysis, it was found out that oak shelterbelts in the north-eastern part of Left-Bank Forest-Steppe absorb 0.8–4.3 tonnes of carbon per ha per year. The highest proportion (91%) of carbon was stored in tree phytomass of the stand (trunks, bark, branches, leaves and roots). Phytomass of tree stands ranges from 51.1 to 291 tonnes per ha and depends on the health and productivity of the shelterbelts. 4 Figs., 5 Tables, 38 Refs.